Social inequality as an enduring phenomenon of general and vocational education - characteristics in the Federal Republic of Germany and international perspectives - Nickolaus, Reinhold [Verfasser]; Gschwendtner, Tobias [Verfasser]; Geißel, Bernd [Verfasser] (My University, 2009)
"This paper seeks to (1) provide an overview, from a macroanalytical perspective, of the characteristics of unequal educational opportunities within an international perspective, (2) set out problems related to social selectivity, in particular within the vocational educational system in Germany and (3) describe examples of the interaction between selection and vocational learning on the basis of empirical investigations. The intention is to illustrate the fundamental problems associated with social inequality at different levels in the educational field and to extract the correlations between selection and vocational learning." (Autorenreferat, BIBB-Doku)
Keywords: S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; T 4.5 Soziologie; Soziale Ungleichheit; Bildungssystem; Berufsausbildung; Bildungschance; Selektion; Empirische Untersuchung; Fallstudie